An Exploratory Study to Investigate the Utility of Clinical Screening for Neurodegenerative Disease in Age-Related Eye Disease Research. Issue 3 (27th September 2022) - Pelak, Victoria S.; Paez, Yosbelkys Martin; Patnaik, Jennifer L.; Holden, Samantha K.; Subramanian, Prem S.; Mathias, Marc T.; Mandava, Naresh; Lynch, Anne M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Unrecognized neurodegenerative diseases (NDD) in age-related eye disease research studies have the potential to confound vision-specific quality of life and retinal optical coherence tomography (OCT) outcome measures. The aim of this exploratory study was to investigate relationships between NDD screening tools and visual outcome measures in a small cohort of controls from the Colorado Age-Related Macular Degeneration Registry (CO-AMD), to consider the utility of future studies. Methods: Twenty-nine controls from the CO-AMD were screened using the Montreal Cognitive Assessment (MoCA), a Colorado Parkinsonian Checklist, and the Lewy Body Composite Risk Score. Univariate and multivariable linear regression modeling was used to assess associations between screening tools and the National Eye Institute Visual Function Questionnaire-25 (VFQ-25) and macular OCT outcome measures, and t tests were used to evaluate outcome measure differences between those with normal vs abnormal MoCA scores. Results: One patient withdrew. The average age was 72.8 years, and 68% were female patients. Ten participants (36%) had abnormal MoCA scores, and their VFQ-25 scores were only 1 point less and not statistically different than those with normal MoCA scores. Macular OCT volumes and thicknesses for retinal nerve fiber layer (RNFL) and retinal ganglion cell layer were consistently and moderately lower for those with abnormal MoCA scores, and a positive association between MoCA and macular RNFL volume was observed, although differences and regression were not significant. Parkinson screening tests were abnormal for only 4 participants and were not associated with OCT or VFQ-25 measures by regression modeling. Conclusions: Given the degree and direction of observed differences, further investigation is warranted regarding the relationship between cognitive screening tools and macular OCT measures in age-related eye disease research, but future investigations regarding the relationship between NDD screening tools and VFQ-25 seem unwarranted.